2021
DOI: 10.1186/s13014-021-01746-0
|View full text |Cite
|
Sign up to set email alerts
|

The watch-and-wait strategy versus surgical resection for rectal cancer patients with a clinical complete response after neoadjuvant chemoradiotherapy

Abstract: Background The watch-and-wait strategy offers a non-invasive therapeutic alternative for rectal cancer patients who have achieved a clinical complete response (cCR) after chemoradiotherapy. This study aimed to investigate the long-term clinical outcomes of this strategy in comparation to surgical resection. Methods Stage II/III rectal adenocarcinoma patients who received neoadjuvant chemoradiotherapy and achieved a cCR were selected from the databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…In our experience, the mean time to the local regrowth during follow-up was 20.8 months (range 10-31 months), with a higher rate of local recurrences within three years compared to surgical groups (15.3% vs. 2.9% and 9.5%). This seems to be lower than results from other authors who reported a larger data series of w&w strategy [12,[29][30][31], and higher than a multicentric registry study [32] with a very large follow-up.…”
Section: Discussioncontrasting
confidence: 71%
“…In our experience, the mean time to the local regrowth during follow-up was 20.8 months (range 10-31 months), with a higher rate of local recurrences within three years compared to surgical groups (15.3% vs. 2.9% and 9.5%). This seems to be lower than results from other authors who reported a larger data series of w&w strategy [12,[29][30][31], and higher than a multicentric registry study [32] with a very large follow-up.…”
Section: Discussioncontrasting
confidence: 71%
“…1 ). After the literature screening, a total of nine studies with 818 patients were included [ 16 24 ]. A total of 339 patients were in the W&W group, and 479 patients were in the TME group.…”
Section: Resultsmentioning
confidence: 99%
“…Although the discovery and use of the 16S rRNA gene have greatly expanded microbiome research, it is still only bacterially selective, limiting this sequencing technique to evaluation of bacterial composition and responses to environmental changes or challenges ( Bäckhed et al, 2005 ). Investigation of the virome, mycobiome, and archaea components of the microbiota broadly and particularly in response to radiation has been lacking ( Rosenberg and Zilber-Rosenberg, 2013 ; Roy and Trinchieri, 2017 ; Liu et al, 2021 ). It is possible that broader insights into the impact of nonbacterial components of the GI microbiota might be obtained through non-targeted shotgun metagenomic sequencing techniques that would be capable of assessing radiation responses in the nonbacterial compartments of the GI microbiota ( Campo et al, 2020 ; Kaźmierczak-Siedlecka et al, 2020 ; Turkington et al, 2021 ).…”
Section: History Of Microbiome Researchmentioning
confidence: 99%
“…As noted above, most studies of the effect of radiation on the GI microbiome have been conducted in the context of cancer radiotherapy, and recent reviews summarize the literature in that context ( Liu et al, 2021 ; Tonneau et al, 2021 ). Indeed, therapeutic abdominopelvic radiation exposure frequently results in intestinal dysfunction and dysbiosis, with acute radiation enteritis complications observed in 50% or more of abdominally irradiated cancer patients ( Touchefeu et al, 2014 ).…”
Section: The Effects Of Radiation On the Microbiomementioning
confidence: 99%